2019
DOI: 10.4103/ijpvm.ijpvm_410_17
|View full text |Cite
|
Sign up to set email alerts
|

Continuous movement monitoring of daily living activities for prevention of diabetic foot ulcer: A review of literature

Abstract: Lower extremity ulcers represent the most ominous, feared, and costly complications of diabetes mellitus. The aim of this review is to highlight the role of daily life physical activities (PAs) and continuous movement monitoring (CMM) in the prevention of foot ulcers. Peripheral neuropathy and peripheral vascular disease are the main causes of foot ulceration and contribute, in turn, to the development of additional risk factors such as foot deformities and/or joint and muscular alterations. Moreover, a defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 74 publications
(179 reference statements)
1
22
0
Order By: Relevance
“…6 Patients with DMPN without an ulcer walk about twice that per day and healthy controls walk 4-5 times as much ( Figure 1). [6][7][8] Despite the fact that high plantar pressures are clearly associated with neuropathic plantar foot skin breakdown, the daily cumulative plantar stress and overall activity level is considerably less for patients that ulcerate compared to patients with DMPN that do not ulcerate and healthy controls. 6,9,10 A likely explanation is that plantar skin tissues become less tolerant of physical stresses in this patient population over time due to the disease progression (i.e.…”
Section: Context For the Patient's Health And Mobility Statusmentioning
confidence: 99%
See 3 more Smart Citations
“…6 Patients with DMPN without an ulcer walk about twice that per day and healthy controls walk 4-5 times as much ( Figure 1). [6][7][8] Despite the fact that high plantar pressures are clearly associated with neuropathic plantar foot skin breakdown, the daily cumulative plantar stress and overall activity level is considerably less for patients that ulcerate compared to patients with DMPN that do not ulcerate and healthy controls. 6,9,10 A likely explanation is that plantar skin tissues become less tolerant of physical stresses in this patient population over time due to the disease progression (i.e.…”
Section: Context For the Patient's Health And Mobility Statusmentioning
confidence: 99%
“…Technology and activity monitors may help measure stress during standing and walking, provide warnings to patients when they are approaching their typical daily static and dynamic weight-bearing levels, and help to prevent problems. 8,12,25 Monitoring plantar skin temperatures was introduced many years ago by Brand 2 and controlled trials have shown daily skin monitoring can help to prevent skin breakdown. 26,27 While temperature monitoring holds promise, one randomized controlled trial to increase activity in people with DMPN reported wide variations in patient skin temperature and frequent false positives.…”
Section: Topics For Future Research To Improve Care In This Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing adverse impacts of gestational diabetes mellitus [95] Physical activity preferences of elderly people with T2D Determine the level of physical activity of elderly people with type 2 diabetes [96] Development of wearable physiologic monitoring devices for use in diabetes management Enhance continuous glucose monitoring [97] Designing an internet-of-things (IoT) and sensor-based in-home monitoring system for assisting diabetes patients Implementation of an internet-of-things (IoT) and wireless sensor system which patients use in their own homes to capture daily activity [98] Continuous movement monitoring of daily living activities Prevention of diabetic foot ulcer [99] Glucose monitoring in individuals with diabetes Long-term implanted sensor/telemetry system and model are used [100] Sensor-based method for glucose monitoring Accuracy, safety and acceptability of the glucose monitoring system in the paediatric population is proposed [101] Continuous glucose monitoring sensors Past and present algorithmic challenges of CGM sensors are introduced [102] Continuous glucose monitoring Use of CGM for adjustment of insulin dosing, and automated interpretation [103] Continuous glucose monitoring Reduce the risk of hypoglycemia [104] T2D management Big data technologies [105] T2D management Predictive models using big data analytics [106] The relationship between diet, physical activity, and T2D Regular PA is a primary component in management of T2D [107] The relationship between physical activity and T2D level of physical activity in people with T2D is analyzed [108] Physical activity and incident type 2 diabetes mellitus Dose-response meta-analysis of prospective cohort studies [109] Physical activity and risk of diabetes PA is associated with reduction in the risk of diabeties [110] Sensor based monitoring of PA to improve glucose management Non-invasive sensors using physiological parameters related to PA to improve glucose monitoring [111] Continuous -Big data, Bandwidth, and computational time: continuous monitoring provides a huge amount of data [115,116].…”
Section: Reference Contributionmentioning
confidence: 99%